Avoiding Poison Apples in the Land of Tomorrow: Patient Satisfaction With Residents Versus Non-Physician Providers in an Obstetrics and Gynecology Academic Medical Center Practice. (October 2017) - Dade, Adrianne; Blanchard, Anita; Young, Danielle; Kupfer, Rachel
Abstract : BACKGROUND: Non-physician providers (NPPs) [physician assistants (PAs), nurse practitioners (APNs), and certified nurse midwives (CNMs)] may be used to supplement duties traditionally filled by Obstetrics & Gynecology (OB/GYN) residents. NPPs provide high level of care and may help protect resident time without compromising patient satisfaction. METHODS: Patients attended to for the majority of their appointments by either NPPs or residents were anonymously surveyed about satisfaction with their health care provider. The survey had 15 questions and was developed in conjunction with a professional survey lab at the University of Chicago. The study was sufficiently powered (80%) to detect equivalency of up to 2.2 points in average scores (out of possible 38) between the NPP and resident group. RESULTS: One hundred sixty-nine total patients were surveyed (resident=103, NPP=66). Patients seen by NPPs were younger ( P <.001) and more often seen for obstetric or postpartum care ( P <.001) compared to patients seen by residents. There was no difference ( P =.48) in overall patient satisfaction if seen by an NPP (mean score: 35.21±4.40) or resident (mean score: 34.72±4.08). Small differences were detected in individual questions. A higher proportion of patients reported having all their questions answered by NPPs (100%) than by residents (93.94%) ( P =.05) and a slightly higher proportion of patients reported having a "fair amount" or "a lot" confidence in NPPs (98.48%) versus residents (91.26%) ( P =.04). DISCUSSION: Patients were equally satisfied with NPP and resident providers.